The Effect of Good Governance Implementation on Discipline, Motivation, and Employee Performance at Tengkayu I Port, Tarakan City - Massahara Massahara; Arif Jauhar Tontowi; Rahmawati Thaha (Journal of Management and Creative Business, 2025)
This study aims to determine the effect of Good Governance implementation on work motivation, work discipline, and employee performance at Tengkayu I Port, Tarakan City. The method used is quantitative. This is a census/population study, with all 67 employees serving as respondents. The analytical tools used were Path Analysis combined with Single Factor Analysis. This combination was applied to examine the structural relationships and the measurement model.The analysis results show that the implementation of Good Governance has a positive and significant effect on work motivation and work discipline. Work motivation and work discipline also have a positive and significant effect on employee performance. Meanwhile, the effect of Good Governance implementation on employee performance is negative and not significant. Indirectly, however, Good Governance implementation has a positive and significant effect on employee performance through the variables of motivation and discipline.The effect of Good Governance implementation on the variation in work motivation was 53%, with the remaining 47% influenced by other factors outside this study. The effect of Good Governance implementation on the variation in work discipline was 45%, with the remaining 55% influenced by other factors outside this study. The combined effect of Good Governance implementation, work motivation, and work discipline on employee performance variation was 66%, while the remaining 34% was influenced by other factors beyond this research.